P04.86 Correlation between activated infiltrating neutrophils and MGMT methylation in patients with diffuse malignant gliomas (MGs). (19th September 2018) - Simonelli, M; Massara, M; Persico, P; Capucetti, A; Lorenzi, E; Lugli, E; Dipasquale, A; Nibali, M; Rossi, M; Bello, L; Locati, M; Bonecchi, R
Abstract: Background: Different immunotherapeutic strategies are currently under clinical evaluation in the context of neuroncology. However, a critical barrier to an effective antitumor immunity is still represented by the wide array of immunosuppressive forces exhibited by malignant gliomas (MGs). The present study aims to perform a comprehensive analysis of infiltrating and circulating leukocyte subsets (lymphocytes, macrophages, dendritic cells, neutrophils) in patients with MGs, identifying the immunological profile of the different histo-molecular subtypes, exploring the functional changes during and after anticancer therapies. Here we report first preliminary data on infiltrating and circulating neutrophils. Materials and Methods: Patients with a clinical-radiological diagnosis of malignant diffuse glioma referring to the NeuroOncological Surgery Unit of the Humanitas Research Hospital between January 2017 and March 2018 were prospectively enrolled in the study. Fresh tumor tissue specimens were collected the day of surgery; peripheral blood samples (PBS) were collected at baseline and then prospectively every two months during active anticancer treatments and then every six months during follow-up. The analysis of the frequency as well as phenotypic and functional characterization of tumor associated neutrophils (TANs) and of circulating neutrophils were performed by flow cytometry. Data were correlated with histology and the molecular markers isocitrate dehydrogenase (IDH) mutation and O(6)-methylguanine-DNA methyltransferase (MGMT) promoter methylation. Results: As per May 2018, 26 out of 84 patients (MG specimens and PBS) plus PBS of 4 healthy donors were analyzed. 12 had IDH wt GBM (n=7 MGMT methylated; n=5 MGMT unmethylated), 5 IDH mut GBM (n=5 MGMT unmethylated), 4 IDH mut anaplastic astrocytoma (n=3 MGMT methylated; n=1 MGMT undetermined), 4 IDH mut anaplastic oligodendrogliomas (n=4 MGMT methylated). TANs represented 5% (SD= 2, 67%) of all CD45+ tumor disaggregated single cell suspensions. No statistically significative differences were found comparing the percentage of TANs (CD45 + CD11b + CD66b + CD16 + ) among different histo-molecular subgroups. However, an increased percentage of activated TANs (CD62L neg CD16 high ) were found in samples from IDH wt GBM patients with methylated MGMT promoter compared to unmethylated ones (p=0, 005). Increased percentages of activated neutrophils were found in PBS from IDH wt GBM patients compared to healthy donors (p=0, 005). Conclusions: An increased number of activated TANs are present in MGMT methylated IDH wt GBM patients compared to unmethylated. IDH wt GBM patients seem to have higher percentages of circulating activated neutrophils compared to healthy donors. Correlation between different subpopulations of TANs, treatment response and clinical outcome will be presented at the meeting.